Analisis Pengaruh Gaya Belajar terhadap Partisipasi Belajar Siswa dalam Pembelajaran Gerak Manipulatif PJOK Sekolah Dasar - Ainunnisa, Finka; Septiadi, Firman; Maulana, Firman (utile: Jurnal Kependidikan, 2025)
Learning styles and student participation are closely related in learning Physical Education, Sport and Health (PJOK) in elementary schools. This study investigates the influence of learning styles on students' participation in Physical Education, Sport and Health (PJOK) lessons in elementary schools. Through a literature study method that explored literature studies on the relationship between learning styles and participation, it was found that learning styles, especially kinesthetic, contribute positively to students' participation level in physical activities. In contrast, students with visual and auditory learning styles tend to show lower participation. This research emphasizes the importance of implementing active learning strategies that suit students' diverse learning styles, such as cooperative models (TGT, STAD, Jigsaw) as well as innovative approaches that integrate stories and games, to increase students' participation. The need for a holistic approach that considers internal factors, such as motivation and learning styles, as well as external factors, including teaching methods and environmental support, was emphasized. Recommendations for future research include testing these findings with a larger sample and exploring more specialized learning strategies to encourage participation of students with diverse learning styles. This study confirmed a significant relationship between learning styles and student participation in physical education teaching, which supports the use of diverse learning strategies to create more inclusive and effective learning experiences.